Gut Microbial Catabolites of Tryptophan Are Ligands and Agonists of the Aryl Hydrocarbon Receptor: A Detailed Characterization - Vyhlídalová, Barbora; Krasulová, Kristýna; Pečinková, Petra; Marcalíková, Adéla; Vrzal, Radim; Zemánková, Lenka; Vančo, Jan; Trávníček, Zdeněk; Vondráček, Jan; Karasová, Martina; Mani, Sridhar; Dvořák, Zdeněk (International journal of molecular sciences, 2020)
We examined the effects of gut microbial catabolites of tryptophan on the aryl hydrocarbon receptor (AhR). Using a reporter gene assay, we show that all studied catabolites are low-potency agonists of human AhR. The efficacy of catabolites differed substantially, comprising agonists with no or low (i3-propionate, i3-acetate, i3-lactate, i3-aldehyde), medium (i3-ethanol, i3-acrylate, skatole, tryptamine), and high (indole, i3-acetamide, i3-pyruvate) efficacies. We displayed ligand-selective antagonist activities by i3-pyruvate, i3-aldehyde, indole, skatole, and tryptamine. Ligand binding assay identified low affinity (skatole, i3-pyruvate, and i3-acetamide) and very low affinity (i3-acrylate, i3-ethanol, indole) ligands of the murine AhR. Indole, skatole, tryptamine, i3-pyruvate, i3-acrylate, and i3-acetamide induced CYP1A1 mRNA in intestinal LS180 and HT-29 cells, but not in the AhR-knockout HT-29 variant. We observed a similar CYP1A1 induction pattern in primary human hepatocytes. The most AhR-active catabolites (indole, skatole, tryptamine, i3-pyruvate, i3-acrylate, i3-acetamide) elicited nuclear translocation of the AhR, followed by a formation of AhR-ARNT heterodimer and enhanced binding of the AhR to the CYP1A1 gene promoter. Collectively, we comprehensively characterized the interactions of gut microbial tryptophan catabolites with the AhR, which may expand the current understanding of their potential roles in intestinal health and disease.
Keywords: Gastrointestinal Microbiome; Ligands; Protein Multimerization; tryptofan; indoly; exprese genu; Cytochrome P-450 CYP1A1; Humans; Promoter Regions, Genetic; ligandy; cytochrom P-450 CYP1A1; receptory aromatických uhlovodíků; Gene Expression; Indoles; Protein Binding; Tryptophan; lidé; zvířata; reportérové geny; myši; Metabolic Networks and Pathways; Mice; Receptors, Aryl Hydrocarbon; Genes, Reporter; vazba proteinů; nádorové buněčné linie; transkripční faktory bHLH; metabolické sítě a dráhy; střevní mikroflóra; Animals; Cell Line, Tumor; promotorové oblasti (genetika); multimerizace proteinu; Basic Helix-Loop-Helix Transcription Factors